Improving pneumonia case-management in Benin: a randomized trial of a multi-faceted intervention to support health worker adherence to Integrated Management of Childhood Illness guidelines - Lama Marcel; Onikpo Faustin; Osterholt Dawn M; Deming Michael S; Rowe Alexander K (BMC, 2009)
Abstract Background Pneumonia is a leading cause of death among children under five years of age. The Integrated Management of Childhood Illness strategy can improve the quality of care for pneumonia and other common illnesses in developing countries, but adherence to these guidelines could be improved. We evaluated an intervention in Benin to support health worker adherence to the guidelines after training, focusing on pneumonia case management. Methods We conducted a randomized trial. After a health facility survey in 1999 to assess health care quality before Integrated Management of Childhood Illness training, health workers received training plus either study supports (job aids, non-financial incentives and supervision of workers and supervisors) or "usual" supports. Follow-up surveys were conducted in 2001, 2002 and 2004. Outcomes were indicators of health care quality for Integrated Management-defined pneumonia. Further analyses included a graphical pathway analysis and multivariable logistic regression modelling to identify factors influencing case-management quality. Results We observed 301 consultations of children with non-severe pneumonia that were performed by 128 health workers in 88 public and private health facilities. Although outcomes improved in both intervention and control groups, we found no statistically significant difference between groups. However, training proceeded slowly, and low-quality care from untrained health workers diluted intervention effects. Per-protocol analyses suggested that health workers with training plus study supports performed better than those with training plus usual supports (20.4 and 19.2 percentage-point improvements for recommended treatment [p = 0.08] and "recommended or adequate" treatment [p = 0.01], respectively). Both groups tended to perform better than untrained health workers. Analyses of treatment errors revealed that incomplete assessment and difficulties processing clinical findings led to missed pneumonia diagnoses, and missed diagnoses led to inadequate treatment. Increased supervision frequency was associated with better care (odds ratio for recommended treatment = 2.1 [95% confidence interval: 1.13.9] per additional supervisory visit). Conclusion Integrated Management of Childhood Illness training was useful, but insufficient, to achieve high-quality pneumonia case management. Our study supports led to additional improvements, although large gaps in performance still remained. A simple graphical pathway analysis can identify specific, common errors that health workers make in the case-management process; this information could be used to target quality improvement activities, such as supervision (ClinicalTrials.gov number NCT00510679).